2016
DOI: 10.3390/met6060127
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Al and Ti Additions on the Structural Stability, Mechanical and Electronic Properties of D8m-Structured Ta5Si3

Abstract: Abstract:In the present study, the influence of substitutional elements (Ti and Al) on the structural stability, mechanical properties, electronic properties and Debye temperature of Ta 5 Si 3 with a D8 m structure were investigated by first principle calculations. The Ta 5 Si 3 alloyed with Ti and Al shows negative values of formation enthalpies, indicating that these compounds are energetically stable. Based on the values of formation enthalpies, Ti exhibits a preferential occupying the Ta 4b site and Al has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…[22][23][24][25] For example, the melting point of Ta 5 Si 3 is up to 2550 • C, which is much higher than the Ni-based superalloys. 26 Furthermore, the calculated bulk elastic modulus, shear modulus, and Young's modulus of Mo 5 Si 3 are 242 GPa, 126 GPa, and 323 GPa. 27 Unfortunately, the low fracture toughness and poor ductility hinder their high-temperature applications.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[22][23][24][25] For example, the melting point of Ta 5 Si 3 is up to 2550 • C, which is much higher than the Ni-based superalloys. 26 Furthermore, the calculated bulk elastic modulus, shear modulus, and Young's modulus of Mo 5 Si 3 are 242 GPa, 126 GPa, and 323 GPa. 27 Unfortunately, the low fracture toughness and poor ductility hinder their high-temperature applications.…”
Section: Introductionmentioning
confidence: 97%
“…The results shown that the addition of Al and Ti improves the ductility of Ta 5 Si 3 matrix. 26 Guo et al studied the effect of Ag doping on the mechanical properties of Nb 5 Si 3 by using the first-principle method. The results show that Ag doping improves the ductility of Nb 5 Si 3 matrix.…”
Section: Introductionmentioning
confidence: 99%